Developing River-based Tourism in Indonesian Local Context: Towards an Agenda of Social Development Implications - Kharis, Ahmad; Langputeh, Sukree (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2024)
This paper aims to revive the discussion on river-based tourism, highlighting its implications for sustainable social development. It is based on an analysis of various studies that have shown a focus on new patterns and strategies for sustainable development in river-based tourism. However, little attention has been given to further exploring these sustainability tools through achieving harmony between human and natural elements. The study adopts a case study approach, focusing on Temulus Village in Indonesia. Data was collected through interviews, observations, and field documentation. The research findings demonstrate that prioritizing the segmentation of river-based tourism development as a key agenda in social development holds intrinsic value as a new tool in transforming rural communities. The research successfully uncovers the harmonious relationship between human interests and nature, thereby contributing to sustainable development through river tourism. Consequently, this study contributes to leveraging local resources for sustainable development, introducing new local indicators that can serve as valuable lessons for future village development.